1989
DOI: 10.1002/ar.1092240205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of calcification: Role of collagen fibrils and collagen‐phosphoprotein complexes in vitro and in vivo

Abstract: Samples of decalcified chicken bone together with varying concentrations of phosphoproteins from bone or egg yolk (phosvitin) were used in vitro as heterogenous nucleators for the induction of Ca-P apatite crystals. The lag time between exposure of the collagen-phosphoprotein complexes and the time nucleation of crystals occurred decreased as the concentration of Ser(P) and Thr(P) increased. Enzymatic cleavage of the phosphate groups by wheat germ and phosphatase reversed this effort, indicating that the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
160
0
7

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(172 citation statements)
references
References 72 publications
5
160
0
7
Order By: Relevance
“…AFM demonstrated that "HA" nanoparticles of about 20 nm were embedded within the gelatine structure so that they split the bed of gelatine nanofibrils into flat bundles of about 45 nm width. HA crystals of similar size are found in natural bone [12][13][14]. Gaps were detected every 200-300 nm along these flat bundles which are also found in the collagen of natural bone [9].…”
Section: Discussionmentioning
confidence: 56%
“…AFM demonstrated that "HA" nanoparticles of about 20 nm were embedded within the gelatine structure so that they split the bed of gelatine nanofibrils into flat bundles of about 45 nm width. HA crystals of similar size are found in natural bone [12][13][14]. Gaps were detected every 200-300 nm along these flat bundles which are also found in the collagen of natural bone [9].…”
Section: Discussionmentioning
confidence: 56%
“…The postulated roles of matrix proteins are diverse: a nucleator by providing certain stereochemical arrangement of charged groups, which is sufficient to lower the activation energy barrier for nucleation of a crystal phase (Glimcher, 1989;Gorski, 1992); or an inhibitor by blocking the growth sites through specific adsorption (Moreno et al, 1979;Termine et al, 1980;Romberg et al, 1986) or by providing spacial constraints as exemplified by the lateral growth of apatitic mineral in calcified turkey tendon (Heywood et al, 1990). Casein phosphoproteins in milk, as cited above, act as a stabilizer of amorphous calcium phosphate in nanometer-sized clusters (Holt et al, 1996).…”
Section: Interaction Between Macromolecules and Calcium Phosphatesmentioning
confidence: 99%
“…This view is also supported by in vitro nucleation experiments, which attempted to simulate the postulated in vivo nucleation substrate of bone tissue by cross-linking the resident phosphoproteins in situ in their native positions and comparing the efficacy (induction or lag time) of this nucleation substrate with samples containing the collagen-phosphoprotein complexes after the covalent phosphate groups were enzymatically cleaved. Not only did the decalcified bone samples containing the collagen-phosphoproteins complexes markedly decrease the nucleation induction time, but this property was lost when the phosphate groups alone were removed enzymatically, leaving the dephosphorylated collagen-phosphoprotein completely intact and, hence, pinpointing the role of the phosphate groups in this in vitro crystal nucleation event (27,28). In addition to their postulated role in calcification, these phosphoproteins have been implicated in many other biological functions (13)(14)(15)(16)29).…”
mentioning
confidence: 99%